2012
DOI: 10.4038/gmj.v17i1.4355
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices regarding dengue fever in a suburban community in Sri Lanka

Abstract: Aims: Methods:Results: Conclusions: Keywords:Dengue is a major public health concern in Sri Lanka. In the recent dengue epidemics, majority of cases of dengue were reported from the Colombo district.To determine the knowledge attitudes and practices (KAP) regarding dengue fever (DF) in a suburban population in the Colombo District.The study was a prospective, cross sectional study and was conducted in 2005/2006 in a suburb of Colombo district. Data was collected using a pre-tested interviewer-administered ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
4
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 6 publications
6
25
4
8
Order By: Relevance
“…Majority of them will had good health seeking behavior by visiting hospital two studies also reported the same results, this lap of knowledge in attaining the protective measures will be decreased by the active health educational programs and propaganda during that season. 15,17 The study has its sets of limitations mainly the possibility of interviewer bias and the drawbacks of convenience sampling. The above observations may be true only for the study population and cannot be generalized to other populations belonging to different socio-economic or cultural backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…Majority of them will had good health seeking behavior by visiting hospital two studies also reported the same results, this lap of knowledge in attaining the protective measures will be decreased by the active health educational programs and propaganda during that season. 15,17 The study has its sets of limitations mainly the possibility of interviewer bias and the drawbacks of convenience sampling. The above observations may be true only for the study population and cannot be generalized to other populations belonging to different socio-economic or cultural backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…Telecommunication facilities are widely used as an effective tool for awareness raising and community mobilization in the fight against dengue [59][60][61]. Often, television and radio have signified their vital importance in knowledge dissemination (regarding vector control, symptoms and patient management of dengue), while allowing the VCE to motivate the local communities to contribute toward community involved dengue control activities [61][62]. Therefore, the percentage of households with access to television and radios is a vital parameter that would enhance the adaptive capacity of local communities, reducing the vulnerability to dengue.…”
Section: Adaptive Capacity Index (Ac)mentioning
confidence: 99%
“…The recurrence of DF each year and the rising number of cases with each epidemic suggest that vector control efforts are probably ineffective and need to be improved. [14]…”
Section: Figure 2: Aedes Aegypti Mosquitomentioning
confidence: 99%